Effect Of Mercuric Chloride Induced Toxicity On Biochemical Changes In Chicken (Kadaknath) - Jain, Nitesh; Shrivastava , A. B.; Jain, Sachin; Jain , N. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The Present Study on the effect of mercuric chloride toxicity on biochemical changes in chicken showed that the serum biomarker enzymes (AST, ALT, ALP, GGT) and biomolecules glucose, total bilirubin creatinine, urea, BUN were increased significantly in both the treatment groups as compared to the control group. At the same time significant reduction in concentration of total plasma protein and serum albumin was observed.